Upaya Pencegahan Pencemaran Akibat Limbah Rumah Tangga di Desa Empat Balai Kecamatan Kuok Kabupaten Kampar - Roza Mildawati; Anas Puri; Sri Hartati Dewi; Heri Ahmadi; Muhammad Ferry Ardianto; Givary Yogi Erlanda (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2022)
This community service activity aims to provide counseling on how to pollute household waste that occurs in the Village of Empat Balai Kec. Kuok Kab. Kampar, thus preventing the potential to become a source of disease and damage to the environment due to household waste that is simply dumped into the environment such as household liquid waste and garbage that is directly dumped into the river without thinking about the impact on the environment, health and economy. The target to be achieved is to make the public aware of the importance of preventing environmental pollution due to household waste, reducing the potential for environmental pollution due to household waste and producing a clean and safe environment from household waste so as to create a clean and comfortable environment. By doing this outreach, it can help the surrounding community as well as provide comfort for the community in the occurrence of household waste water pollution. For the next program, it is important to conduct outreach by surveying directly the place where water is polluted due to household waste.